APAKAH TEORI DEMAND-FOLLOWING ATAUKAH TEORI SUPPLY-LEADING YANG BERLAKU DI ASIA PASIFIK? - nuri rosmika rosmika (EKOMBIS: JURNAL FAKULTAS EKONOMI, 2022)
This study analyze is the demand-following theory or supply-leading theory prevails in the Asia Pacific region. The data used is panel nine countries in 2003-2019. This study focuses on lowermiddle income countries in the Asia Pacific region: Indonesia, Cambodia, Philippines, Myanmar, Mongolia, Papua New Guinea, Solomon Islands, Timor Leste, and Vanuatu. Analysis tool is using the Granger and VAR causality test. As a result, the demand-following theory that applies to the nine Asia Pacific countries with lower middle income. Therefore, governments in thiscountries should focus on improving the economy in the non-financial sectors. Thus, the financial sector will automatically grow.